2021
DOI: 10.1159/000519069
|View full text |Cite
|
Sign up to set email alerts
|

Snapping Scapula Syndrome in the Setting of Elastofibroma Dorsi: A Case Report

Abstract: A 54-year-old woman presented with a 15-year history of progressively worsening left snapping scapula syndrome (SSS) in the setting of ipsilateral elastofibroma dorsi. Her pain was refractory to multiple conservative measures. She was successfully treated with focal ultrasound-guided corticosteroid injection to the superomedial border of the scapula. There was demonstrable improvement in findings between pre- and post-procedural MRI examinations. Despite the underlying cause of SSS, trials of nonoperative trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…An ultrasound is generally the first line of examination, as it poses no radiation damage to the patient, followed by CT and MRI scans. MRI, although not routinely required, can elevate diagnostic confidence as a result of its good soft tissue contrast (1,13). As per the standard diagnostic approach, an ultrasound was initially performed in the patient described in the present study, which revealed a solid mass with a size of 10x8x3 cm at the posterior-lateral aspect of the lower right chest wall.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…An ultrasound is generally the first line of examination, as it poses no radiation damage to the patient, followed by CT and MRI scans. MRI, although not routinely required, can elevate diagnostic confidence as a result of its good soft tissue contrast (1,13). As per the standard diagnostic approach, an ultrasound was initially performed in the patient described in the present study, which revealed a solid mass with a size of 10x8x3 cm at the posterior-lateral aspect of the lower right chest wall.…”
Section: Discussionmentioning
confidence: 93%
“…Pain was the chief complaint in symptomatic individuals with other symptoms, such as discomfort and fatigue. Imaging analyses, such as ultrasound, CT scan and magnetic resonance imaging (MRI) were frequently used for diagnosis (11)(12)(13)(14)(15)(16)(17). Some studies utilized more than one imaging technique to further analyze the lesion and made a comparison between them (3,(9)(10)(11)(12)16).…”
Section: Discussionmentioning
confidence: 99%